Magnesium / magnesium alloy material of antibacterial and anticorrosive composite coating and preparation method of magnesium / magnesium alloy material
By applying antibacterial and anticorrosion composite coating on magnesium/magnesium alloy materials, combined with microarc oxidation coating, photothermal, metal ion synergistic antibacterial coating or self-sacrificing zinc oxide coating, the shortcomings of magnesium alloy products in corrosion resistance, biocompatibility, etc. are solved, and high-performance medical magnesium alloy materials are achieved.
Patent Information
- Application Number
- CN202411465485.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-25
AI Technical Summary
The existing magnesium alloy products have shortcomings in comprehensive performance indicators such as corrosion resistance, biocompatibility, binding strength and durability, and the actual use effect is not ideal.
A magnesium/magnesium alloy material with an antibacterial anticorrosion composite coating includes a magnesium/magnesium alloy matrix, a microarc oxidation coating and a photothermal, photodynamic, metal ion synergistic antibacterial anticorrosion coating or a self-sacrificial zinc oxide coating. The coating forms a two-dimensional planar structure by loading porphyrin or perylene organic ligands with a π aromatic system to coordinate with functional metal ions, thereby enhancing antibacterial and corrosion resistance.
实现了镁/镁合金材料的良好生物相容性和抗菌性能,同时提高了其抗腐蚀性和耐久性,满足医用镁合金的高性能需求。
Smart Images

Figure CN119507008A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnesium alloy coatings, and in particular relates to a magnesium / magnesium alloy material of an antibacterial and anticorrosive composite coating and a preparation method thereof. Background Art
[0002] Magnesium and magnesium alloys are considered to be a promising biomedical degradable metal material due to their excellent biocompatibility, mechanical compatibility, biodegradability, and osteogenic, antibacterial and antitumor functions. However, the excessively fast degradation rate of magnesium and magnesium alloys directly limits their clinical application. Controlling tissue uniformity is the key to achieving uniform degradation of magnesium and magnesium alloys. Current approaches to improving the degradation rate of magnesium and magnesium alloys include alloying, machining and surface modification. For magnesium and magnesium alloys with typical close-packed hexagonal structures, it is very difficult to obtain uniform tissues through alloying and machining due to their small number of slip systems and relatively negative standard electrode potentials. Surface modification has become the only way to regulate magnesium and magnesium alloys.
[0003] At present, surface modification has become the most commonly used technical means in the prior art. In order to achieve sufficient protective performance, the coating must be uniform, dense and have good adhesion to the substrate. Moreover, as a functional material, medical magnesium alloys particularly need to design new coatings with excellent corrosion resistance, good biocompatibility and excellent antibacterial ability from the perspective of integrating coating structure and function. Up to now, people have studied a variety of surface modification coatings and surface modification technologies, and developed numerous products. However, the surface-modified magnesium alloy products manufactured by the prior art all have many deficiencies, which are mainly manifested in the lack of comprehensive performance indicators such as corrosion resistance, biocompatibility, bonding strength, durability, etc., and the actual use effect is not very ideal. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a magnesium / magnesium alloy material with an antibacterial and anti-corrosion composite coating and a preparation method thereof. The prepared magnesium / magnesium alloy material has good biocompatibility and, combined with metal ions, has antibacterial and anti-corrosion properties and can be used as a medical magnesium alloy.
[0005] The technical solutions adopted are:
[0006] A magnesium / magnesium alloy material with an antibacterial and anticorrosive composite coating comprises a magnesium / magnesium alloy substrate from the inside to the outside, and also comprises a micro-arc oxidation coating and an antibacterial and anticorrosive coating; the antibacterial and anticorrosive coating is a photothermal, photodynamic and metal ion synergistic antibacterial and anticorrosive coating, or a self-sacrificial zinc oxide coating and a photothermal, photodynamic and metal ion synergistic antibacterial and anticorrosive coating; wherein the photothermal, photodynamic and metal ion synergistic antibacterial coating is a hybrid coating with a two-dimensional planar structure formed by loading a π aromatic system and a centrally symmetrical porphyrin organic ligand, a functional ligand with a coordination site and a spatial volume smaller than that of the porphyrin organic ligand, and a functional polymer ligand with a coordination site coordinated with a functional metal ion; the self-sacrificial zinc oxide coating is an in-situ grown zinc oxide coating, and the photothermal, photodynamic and metal ion synergistic antibacterial coating is a hybrid coating with a two-dimensional planar structure formed by loading a π aromatic system and a centrally symmetrical perylene organic ligand coordinated with a functional metal ion.
[0007] Preferably, the micro-arc oxidation coating is a phytic acid-based micro-arc oxidation coating.
[0008] Preferably, the porphyrin organic ligand with a π aromatic system and central symmetry carried by the photothermal, photodynamic, and metal ion synergistic antibacterial and anticorrosive composite coating is any one of meso-tetrakis(4-carboxyphenyl)porphyrin, 5,10,15,20-tetrakis(4-aminophenyl)porphyrin, tetraaldehydephenylporphyrin, 5,10,15,20-tetrakis(4-methoxyphenyl)porphyrin, 5,10,15,20-tetrakis(4-cyanophenyl)porphyrin, 5,10,15,20-tetrakis(3,5-dihydroxyphenyl)porphyrin, and 5,10,15,20-tetrakis(4-hydroxyphenyl)-21H,23H-porphyrin; the functional ligand having a coordination site and a smaller spatial volume than the porphyrin organic ligand is pyrazine or 2-methylimidazole; and the functional polymer ligand having a coordination site is polyvinylpyrrolidone.
[0009] Preferably, the centrosymmetric perylene organic ligand having a π aromatic system is any one of 3,4,9,10-perylenetetracarboxamide diimide, perylene-3,4,9,10-tetracarboxylic dianhydride or 4,4',4",4'-(perylene-2,5,8,11-tetrayl)tetrabenzoic acid.
[0010] Preferably, the functional metal ions are zinc ions, strontium ions, gallium ions, manganese ions, cerium ions, zirconium ions and selenium ions.
[0011] A method for preparing a magnesium / magnesium alloy material with an antibacterial and anticorrosive composite coating comprises the following steps:
[0012] (a) Pretreatment:
[0013] The magnesium alloy substrate was sanded with sandpaper until there were no obvious scratches on the surface, washed with deionized water and anhydrous ethanol, dried with cold air, placed in an oven, and taken out after constant temperature drying;
[0014] (b) Preparation of micro-arc oxidation coating:
[0015] (b1) dissolving phytic acid and sodium hydroxide in deionized water to prepare a micro-arc oxidation electrolyte solution;
[0016] (b2) clamping the pretreated magnesium / magnesium alloy substrate between an anode and placing it in a micro-arc oxidation electrolyte solution, then passing a current and applying a high voltage to grow a phytic acid system micro-arc oxidation coating on the surface of the magnesium / magnesium alloy substrate;
[0017] (c) Preparation of antibacterial and anticorrosive coating:
[0018] A mixed solution of a hybrid coating having a two-dimensional planar structure formed by coordination of a π-aromatic system and a centrally symmetrical porphyrin organic ligand, a functional ligand having a coordination site and a smaller spatial volume than the porphyrin organic ligand, and a functional polymer ligand having a coordination site and a functional metal ion is prepared, for example, a mixed solution of NN-dimethylformamide and alcohol containing zinc nitrate hexahydrate, meso-tetrakis(4-carboxyphenyl)porphine, pyrazine and polyvinylpyrrolidone is prepared;
[0019] The magnesium / magnesium alloy coated with the micro-arc oxidation coating prepared in step (b) is immersed in the prepared mixed solution of the hybrid coating (a mixed solution of N,N-dimethylformamide and alcohol), and subjected to hydrothermal treatment at 70-90° C. for 20-25 h, and a layer of photothermal, photodynamic, and metal ion synergistic antibacterial coating is in situ grown on the surface of the micro-arc oxidation coating with the micro-arc oxidation coating as an intermediate layer, and the coating is taken out, rinsed, and blown dry;
[0020] The magnesium / magnesium alloy material covered with the micro-arc oxidation coating and the photothermal, photodynamic, and metal ion synergistic antibacterial and anticorrosion coating is placed in an oven for drying, and taken out after constant temperature drying treatment to obtain a magnesium / magnesium alloy material with a photothermal, photodynamic, and metal ion synergistic antibacterial and anticorrosion composite coating;
[0021] Alternatively, (c1) is prepared from a sacrificial zinc oxide coating:
[0022] Prepare zinc nitrate solution;
[0023] The magnesium / magnesium alloy coated with the micro-arc oxidation coating prepared in step (b) is immersed in the zinc nitrate solution prepared in step (c1), and subjected to hydrothermal treatment at 110-130° C. for 3-5 hours to in-situ grow a layer of zinc oxide coating on the surface of the micro-arc oxidation coating, and then taken out, rinsed, and dried;
[0024] The prepared magnesium / magnesium alloy coated with the micro-arc oxidation coating and the zinc oxide coating is placed in an oven for drying, and taken out after being dried at a constant temperature;
[0025] (c2) Preparation of a hybrid coating in which a π-aromatic system and a centrosymmetric perylene organic ligand coordinated with a functional metal ion form a two-dimensional planar structure:
[0026] Prepare a deionized aqueous solution containing a perylene organic ligand having a π aromatic system and being centrosymmetric and 2-methylimidazole, for example, a deionized aqueous solution of 3,4,9,10-perylenetetracarboxylic acid diimide and 2-methylimidazole;
[0027] The micro-arc oxidation magnesium / magnesium alloy coated with zinc oxide coating prepared in step (c1) is immersed in a deionized water solution containing a perylene organic ligand loaded with a π aromatic system and central symmetry and 2-methylimidazole, and subjected to hydrothermal treatment at 110-130° C. for 3-5 hours, and a layer of photothermal and metal ion synergistic antibacterial coating is in situ grown on the surface of the micro-arc oxidation coating with the zinc oxide coating as a self-sacrificial layer, and the coating is taken out, rinsed, and blown dry;
[0028] The prepared magnesium / magnesium alloy material covered with a micro-arc oxidation coating, a self-sacrificial zinc oxide coating, and a photothermal and metal ion synergistic antibacterial coating is placed in an oven for drying, and taken out after constant temperature drying treatment to obtain a magnesium / magnesium alloy material with a photothermal and metal ion synergistic antibacterial and anticorrosive composite coating.
[0029] Preferably, in step (b1), the concentration of phytic acid is 5-10 g / L, and the concentration of sodium hydroxide is 5-15 g / L; in step (b2), the voltage is 400 V, the current is 1 A, and the duty cycle is 20%.
[0030] Preferably, the concentration of zinc nitrate hexahydrate is 0.34-0.35 g / L, the concentration of meso-tetrakis(4-carboxyphenyl)porphine is 0.31-0.32 g / L, the concentration of pyrazine is 0.10-0.11 g / L, the concentration of polyvinylpyrrolidone is 1.32-1.33 g / L, and the volume ratio of N,N-dimethylformamide and alcohol in the mixed solution is 3:1.
[0031] Preferably, the concentration of zinc nitrate is 10-11 g / L; the concentration of 3,4,9,10-perylenetetracarboxylic acid diimide is 0.8-1.2 g / L; and the concentration of 2-methylimidazole is 100-110 g / L.
[0032] Preferably, the total thickness of the micro-arc oxidation coating and the antibacterial and anticorrosive coating is 5 to 6 um.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The magnesium / magnesium alloy surface antibacterial and anticorrosive composite coating prepared by the present invention is covered with a micro-arc oxidation coating and a photothermal, photodynamic, and metal ion synergistic antibacterial and anticorrosive composite coating, and its structure is a two-dimensional planar structure parallel to the surface of the magnesium / magnesium alloy substrate, and the structure is dense and uniform, which can maximize the performance of the two-dimensional material in blocking corrosive media, not only giving the coating excellent corrosion resistance, but also having good biocompatibility and antibacterial properties; the micro-arc oxidation coating and the photothermal, metal ion synergistic antibacterial composite coating covered with self-sacrificial zinc oxide are in a two-dimensional lamellar structure, stacked layer by layer, with a dense and uniform structure, and not only having excellent corrosion resistance, but also having good biocompatibility and photothermal antibacterial properties;
[0035] The method for preparing the magnesium / magnesium alloy surface composite coating provided by the present invention has simple process, easily controllable conditions and low production cost, and is worthy of wide-scale promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The surface scanning electron microscope photograph of the AZ31 magnesium alloy material with a micro-arc oxidation coating (MAO) prepared in Comparative Example 1 and its enlarged photograph and the surface scanning electron microscope photograph of the AZ31 magnesium alloy material with a composite coating prepared in Example 1 and its enlarged photograph;
[0037] Figure 2 These are XRD spectra of the AZ31 magnesium alloy material with a micro-arc oxidation coating (MAO) prepared in Comparative Example 1 and the AZ31 magnesium alloy material with a composite coating prepared in Example 1;
[0038] Figure 3 It is a potentiodynamic polarization curve diagram of an AZ31 magnesium alloy substrate, an AZ31 magnesium alloy material with a micro-arc oxidation coating (MAO) prepared in Comparative Example 1, and an AZ31 magnesium alloy material with a composite coating prepared in Example 1;
[0039] Figure 4 Figure (a) shows the impedance curves of the AZ31 magnesium alloy material with a micro-arc oxidation coating prepared in Comparative Example 1 and the composite coating prepared in Example 1; Figure (b) shows the impedance curves of the magnesium alloy AZ31 substrate without coating and the AZ31 magnesium alloy material with a micro-arc oxidation coating prepared in Comparative Example 1;
[0040] Figure 5 Figure (a) is a temperature rise curve of the AZ31 magnesium alloy substrate and the AZ31 magnesium alloy material with a composite coating obtained in Example 1 in air; Figure (b) is a temperature rise curve of the AZ31 magnesium alloy substrate and the AZ31 magnesium alloy material with a composite coating obtained in Example 1 in a solution;
[0041] Figure 6is a cyclic photothermal curve of the AZ31 magnesium alloy material with a composite coating prepared in Example 1 excited by 808nm near-infrared light in air;
[0042] Figure 7 The scanning electron microscope photographs of the surface of the AZ31 magnesium alloy material with a micro-arc oxidation coating (MAO) prepared in Comparative Example 2, the scanning electron microscope photographs of the surface and cross-section of the AZ31 magnesium alloy material covered with a micro-arc oxidation coating of self-sacrificial zinc oxide prepared in Comparative Example 3, and the scanning electron microscope photographs of the surface and cross-section of the AZ31 magnesium alloy material with a composite coating prepared in Example 1;
[0043] Figure 8 The XRD patterns of the AZ31 magnesium alloy material with a micro-arc oxidation coating (MAO) prepared in Comparative Example 2, the micro-arc oxidation coating covered with self-sacrificial zinc oxide prepared in Comparative Example 3, and the AZ31 magnesium alloy material with a composite coating prepared in Example 1;
[0044] Fig. 9 It is a potentiodynamic polarization curve diagram of the AZ31 magnesium alloy substrate, the AZ31 magnesium alloy material with a micro-arc oxidation coating (MAO) prepared in Comparative Example 2, and the AZ31 magnesium alloy material with a composite coating prepared in Example 11;
[0045] Fig.10 The left figure is the impedance curve of the AZ31 magnesium alloy material with micro-arc oxidation coating and photothermal antibacterial coating prepared in Example 1; the right figure is the impedance curve of the magnesium alloy AZ31 substrate without coating and the MAO coating prepared in Comparative Example 2;
[0046] Fig.11 are the heating curves of the AZ31 magnesium alloy substrate and the AZ31 magnesium alloy material with the composite coating prepared in Example 11 under different environments;
[0047] Fig.12 is a cyclic photothermal curve of the AZ31 magnesium alloy material with a composite coating prepared in Example 11 excited by 808nm near-infrared light in air;
[0048] Fig.13 These are the test results of the antibacterial properties of the AZ31 magnesium alloy substrate, the AZ31 magnesium alloy material with a micro-arc oxidation coating (MAO) prepared in Comparative Example 2, and the AZ31 magnesium alloy material with a composite coating prepared in Example 11 under no light and light conditions. DETAILED DESCRIPTION
[0049] In order to clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings required for use in the embodiments or the prior art description are briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. The parts not described in the present invention can be implemented by adopting or drawing on existing technologies.
[0050] The present invention is described in detail below with reference to the accompanying drawings.
[0051] Example 1
[0052] A method for preparing a magnesium / magnesium alloy material with an antibacterial and anticorrosive composite coating, specifically a method for preparing a magnesium / magnesium alloy material with a photothermal, photodynamic, and metal ion synergistic antibacterial and anticorrosive composite coating, comprising the following steps:
[0053] Step 1: Preprocessing
[0054] The magnesium alloy substrate was polished with 1500# water-based SiC sandpaper until there were no obvious scratches on the surface, cleaned with deionized water and anhydrous ethanol and dried with cold air, placed in an oven, and dried at a constant temperature of 60°C for 40 minutes before being taken out.
[0055] Step 2: Preparation of micro-arc oxidation coating
[0056] (1) 8 g of phytic acid and 10 g of sodium hydroxide were dissolved in deionized water to prepare 1 L of micro-arc oxidation electrolyte solution;
[0057] (2) The pretreated magnesium / magnesium alloy substrate is clamped between the anode and immersed in a micro-arc oxidation electrolyte. A phytic acid system micro-arc oxidation ceramic coating is prepared by applying a constant current method at a duty cycle of 20% and a current of 1A to a voltage of 380V.
[0058] Step 3: Prepare a hybrid coating with a two-dimensional planar structure formed by the coordination of a functional polymer ligand with a large π aromatic system and central symmetry, a functional ligand with multiple coordination sites and a spatial volume much smaller than that of the porphyrin organic ligand, and a functional metal ion.
[0059] (1) 0.344 g of zinc nitrate hexahydrate, 0.313 g of meso-tetrakis(4-carboxyphenyl)porphine, 0.109 g of pyrazine, and 1.328 g of polyvinylpyrrolidone were added to anhydrous ethanol and N,N-dimethylformamide to prepare a 1 L mixed solution containing zinc nitrate hexahydrate, meso-tetrakis(4-carboxyphenyl)porphine, pyrazine, and polyvinylpyrrolidone, wherein the volume ratio of anhydrous ethanol to N,N-dimethylformamide was 3:1;
[0060] (2) The magnesium / magnesium alloy coated with the micro-arc oxidation coating is immersed in a mixed solution containing zinc nitrate hexahydrate, meso-tetra(4-carboxyphenyl)porphine, pyrazine and polyvinylpyrrolidone, and solvent thermally treated at 80°C for 24 hours, then taken out, rinsed and blown dry, and then placed in an oven and dried at a constant temperature of 60°C for 30 minutes to obtain a magnesium / magnesium alloy material having a micro-arc oxidation coating and a photothermal, photodynamic, and metal ion synergistic antibacterial and anticorrosive coating, that is, a magnesium / magnesium alloy material covered with a composite coating.
[0061] Comparative Example 1
[0062] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, only an AZ31 magnesium alloy material covered with a micro-arc oxidation coating is prepared, and the preparation steps of the micro-arc oxidation coating are the same as those of Example 1.
[0063] Example 2
[0064] The difference between Example 2 and Example 1 is that in this example, the porphyrin-based organic ligand having a relatively large π aromatic system and centrosymmetry is tetraaldehyde phenylporphyrin.
[0065] Example 3
[0066] The difference between Example 3 and Example 1 is that the porphyrin-based organic ligand with a relatively large π aromatic system and centrosymmetry in this example is 5,10,15,20-tetrakis(4-methoxyphenyl)porphyrin.
[0067] Example 4
[0068] The difference between Example 4 and Example 1 is that the porphyrin-based organic ligand with a relatively large π aromatic system and centrosymmetry in this example is 5,10,15,20-tetrakis(4-cyanophenyl)porphyrin.
[0069] Example 5
[0070] The difference between Example 5 and Example 1 is that the porphyrin-based organic ligand with a relatively large π aromatic system and centrosymmetry in this example is 5,10,15,20-tetrakis(3,5-dihydroxyphenyl)porphyrin.
[0071] Example 6
[0072] The difference between Example 6 and Example 1 is that the porphyrin-based organic ligand with a relatively large π aromatic system and centrosymmetry in this example is 5,10,15,20-tetrakis(4-hydroxyphenyl)-21H,23H-porphine.
[0073] Example 7
[0074] The difference between Example 7 and Example 1 is that the porphyrin-based organic ligand with a relatively large π aromatic system and centrosymmetry in this example is 5,10,15,20-tetrakis(4-aminophenyl)porphyrin.
[0075] Example 8
[0076] The difference between Example 8 and Example 1 is that in this example, the functional ligand having a coordination site and a smaller spatial volume than the porphyrin organic ligand is 2-methylimidazole.
[0077] Example 9
[0078] The difference between Example 9 and Example 1 is that the functional metal ions in this example are strontium ions.
[0079] Example 10
[0080] The difference between Example 10 and Example 1 is that the functional metal ions in this example are gallium ions.
[0081] Embodiment 11
[0082] The difference between Example 11 and Example 1 is that the functional metal ion in this example is a manganese ion.
[0083] Example 12
[0084] The difference between Example 12 and Example 1 is that the functional metal ions in this example are cerium ions.
[0085] Embodiment 13
[0086] The difference between Example 13 and Example 1 is that the functional metal ion in this example is zirconium ion.
[0087] Embodiment 14
[0088] The difference between Example 14 and Example 1 is that the functional metal ion in this example is a selenium ion.
[0089] Example 1 was selected as a representative example, and its related performance was tested. Figure 1-6 shown.
[0090] like Figure 1 As shown, Figure 1 (a) is a surface scanning electron microscope photograph of the AZ31 magnesium alloy material with a micro-arc oxidation coating (MAO) prepared in Comparative Example 1, Figure 1 (b) is a local enlarged surface scanning electron microscope photograph of the AZ31 magnesium alloy material with micro-arc oxidation coating (MAO) prepared in Comparative Example 1, Figure 1 (c) is a surface scanning electron microscope photo of AZ31 magnesium alloy material with composite coating. Figure 1 (d) is a local enlarged surface scanning electron microscope photo of AZ31 magnesium alloy material with composite coating. Figure 1 It can be seen from (a), (b), (c), and (d) that there are many holes and cracks on the surface of the micro-arc oxidation coating. The corrosive medium will contact the substrate through the holes and cracks to cause corrosion, thereby affecting the corrosion resistance of the micro-arc oxidation coating. The surface of the composite coating with micro-arc oxidation coating and photothermal, photodynamic, and metal ion synergistic antibacterial and corrosion resistance has completely covered the holes and cracks. The generated two-dimensional flaky structure parallel to the substrate is relatively thin, and the internal longitudinally growing two-dimensional flaky structure can be observed through the gap. The parallel and longitudinally growing two-dimensional flaky structures work together to block the invasion of corrosive media and endow the magnesium / magnesium alloy substrate with excellent corrosion resistance.
[0091] like Figure 2 As shown, the XRD patterns of the AZ31 magnesium alloy material with micro-arc oxidation coating (MAO) prepared in Comparative Example 1 and the AZ31 magnesium alloy material with composite coating prepared in Example 1 are shown in FIG. Figure 2 It can be seen that the AZ31 magnesium alloy material with composite coating shows the peak position of Zn-TCPP MOF, but the peak position shown is not the typical Zn-TCPP peak position, indicating that polyvinyl pyrrolidone participates in the growth of Zn-TCPP MOF and changes the growth direction. The composite coating mainly consists of micro-arc oxidation coating and photothermal, photodynamic, and metal ion synergistic antibacterial coating.
[0092] like Figure 3 As shown, the potentiodynamic polarization curves of the AZ31 magnesium alloy substrate, the AZ31 magnesium alloy material with micro-arc oxidation coating (MAO) prepared in Comparative Example 1, and the AZ31 magnesium alloy material with composite coating prepared in Example 1 are shown. Figure 3 It can be seen that the self-corrosion current density of the AZ31 magnesium alloy material with the composite coating prepared in Example 1 is significantly reduced, from 6.819×10-6A / cm2 to 2.354×10-7A / cm2, indicating that the magnesium alloy material with the composite coating has excellent corrosion resistance.
[0093] like Figure 4 As shown, (a) is the impedance curve of the AZ31 magnesium alloy substrate, the AZ31 magnesium alloy material with micro-arc oxidation coating (MAO) prepared in Comparative Example 1, and the AZ31 magnesium alloy material with composite coating prepared in Example 1, and (b) is a partial enlarged view of the left figure. Figure 4It can be seen from the comparison that the AC impedance of the AZ31 magnesium alloy material with the composite coating prepared in Example 1 is significantly increased compared with the magnesium alloy AZ31 without coating. The AC impedance of the AZ31 magnesium alloy material with the composite coating prepared in Example 1 is also significantly increased compared with the magnesium alloy AZ31 with micro-arc oxidation coating, indicating that the magnesium alloy material with the composite coating has excellent corrosion resistance.
[0094] like Figure 5 Shown are the temperature rise curves of the AZ31 magnesium alloy substrate and the AZ31 magnesium alloy material with a composite coating prepared in Example 1 in air and Hank's solution, respectively. It can be seen from the figure that the magnesium alloy with a composite coating has excellent light and thermal properties.
[0095] like Figure 6 The cyclic photothermal curve of the AZ31 magnesium alloy material with composite coating prepared in Example 1 excited by 808nm near-infrared light in air is shown. Figure 6 It can be seen that the composite coating has excellent light and heat stability.
[0096] Embodiment 15
[0097] A method for preparing a magnesium / magnesium alloy material with an antibacterial and anticorrosive composite coating, specifically a method for preparing a magnesium / magnesium alloy material with a photothermal and metal ion synergistic antibacterial and anticorrosive composite coating, specifically comprising the following steps:
[0098] Step 1: Preprocessing:
[0099] First, the AZ31 magnesium alloy substrate was polished until there were no obvious scratches on the surface, cleaned with deionized water or anhydrous ethanol, and dried with cold air.
[0100] Step 2: Preparation of micro-arc oxidation coating:
[0101] (1) 8 g of phytic acid and 10 g of sodium hydroxide were dissolved in deionized water to prepare 1 L of micro-arc oxidation electrolyte solution;
[0102] (2) The pretreated magnesium / magnesium alloy substrate is clamped between the anode and immersed in a micro-arc oxidation electrolyte. A phytic acid system micro-arc oxidation ceramic coating is prepared by applying a constant current method at a duty cycle of 20% and a current of 1A to a voltage of 380V.
[0103] Step 3: Preparation of self-sacrificial zinc oxide coating:
[0104] (1) Add 11.9 g of zinc nitrate to deionized water to prepare 1 L of zinc nitrate solution;
[0105] (2) The magnesium / magnesium alloy covered with the micro-arc oxidation coating is immersed in a zinc nitrate solution, hydrothermally treated at 120°C for 4 hours, taken out, rinsed and blown dry, and then placed in an oven and dried at a constant temperature of 60°C for 30 minutes to obtain a magnesium / magnesium alloy material having a self-sacrificial zinc oxide coating and a micro-arc oxidation coating, that is, a micro-arc oxidation magnesium / magnesium alloy material covered with a self-sacrificial zinc oxide coating is obtained.
[0106] Step 4: Prepare a hybrid coating that is loaded with a large π aromatic system and a centrally symmetrical perylene organic ligand coordinated with functional metal ions to form a two-dimensional planar structure:
[0107] (1) 1 g of 3,4,9,10-perylenetetracarboxylic acid diimide and 103.4 g of 2-methylimidazole were added to deionized water to prepare a 1 L solution containing 3,4,9,10-perylenetetracarboxylic acid diimide and 2-methylimidazole;
[0108] (2) The micro-arc oxidation magnesium / magnesium alloy covered with a self-sacrificial zinc oxide coating is immersed in a solution containing 3,4,9,10-perylenetetracarboxylic acid diimide and 2-methylimidazole, and hydrothermally treated at 120°C for 4 hours, taken out, rinsed and blown dry, and then placed in an oven and dried at a constant temperature of 60°C for 30 minutes to obtain a magnesium / magnesium alloy material having a micro-arc oxidation coating and a photothermal and metal ion synergistic antibacterial coating, that is, a magnesium / magnesium alloy material covered with a composite coating.
[0109] The average thickness of the micro-arc oxidation coating of the self-sacrificial zinc oxide prepared by the third step is about 4.5 um.
[0110] The average thickness of the composite coating prepared by the fourth step is about 5.5 um.
[0111] Example 16
[0112] The difference between Example 16 and Example 11 is that in the example, the perylene organic ligand having a relatively large π aromatic system and central symmetry is perylene-3,4,9,10-tetracarboxylic dianhydride.
[0113] Embodiment 17
[0114] The difference between Example 17 and Example 11 is that in this example, the perylene organic ligand having a relatively large π aromatic system and central symmetry is 4,4',4",4"'-(perylene-2,5,8,11-tetrayl)tetrabenzoic acid.
[0115] Embodiment 18
[0116] The difference between Example 18 and Example 15 is that the functional metal ions in this example are strontium ions.
[0117] Embodiment 19
[0118] The difference between Example 19 and Example 15 is that the functional metal ions in this example are gallium ions.
[0119] Embodiment 20
[0120] The difference between Example 20 and Example 15 is that the functional metal ion in this example is a manganese ion.
[0121] Embodiment 21
[0122] The difference between Example 21 and Example 15 is that the functional metal ion in this example is a cerium ion.
[0123] Embodiment 22
[0124] The difference between Example 22 and Example 15 is that the functional metal ion in this example is a zirconium ion.
[0125] Embodiment 23
[0126] The difference between Example 23 and Example 15 is that the functional metal ion in this example is a selenium ion.
[0127] Comparative Example 2
[0128] The difference between Comparative Example 2 and Example 15 is that in Comparative Example 2, only AZ31 magnesium alloy material covered with a micro-arc oxidation coating is prepared, and the preparation steps of the micro-arc oxidation coating are the same as those of Example 15.
[0129] Comparative Example 3
[0130] The difference between Comparative Example 3 and Example 15 is that in this comparative example, a micro-arc oxidized AZ31 magnesium / magnesium alloy material coated with a self-sacrificial zinc oxide coating is prepared, and the preparation steps of the self-sacrificial zinc oxide coating are the same as those of Example 15.
[0131] Example 11 was selected as a representative example, and its related performance was tested. Figure 7-13 shown.
[0132] like Figure 7 As shown, Figure 7 (a) is a surface scanning electron microscope photograph of the AZ31 magnesium alloy material with a micro-arc oxidation coating (MAO) prepared in Comparative Example 2, Figure 7 (b) is a surface scanning electron microscope photograph of the micro-arc oxidized AZ31 magnesium / magnesium alloy material with a self-sacrificial zinc oxide coating prepared in Comparative Example 3, Figure 7 (c) is a surface scanning electron microscope photo of AZ31 magnesium alloy with composite coating. Figure 7It can be seen from (a), (b), and (c) that there are many holes on the surface of the micro-arc oxidation coating. The corrosive medium will contact the substrate through the holes to cause corrosion, thereby affecting the corrosion resistance. The surface of the self-sacrificial zinc oxide coating is mostly zinc oxide nanosheets and nanorods, but the zinc oxide coating is relatively thin, and the underlying micro-arc oxidation coating can still be clearly seen. The surface of the composite coating with micro-arc oxidation coating and photothermal and metal ion synergistic antibacterial coating has completely covered the holes, and the generated two-dimensional flaky molecules are stacked layer by layer to eventually form a relatively uniform and dense two-dimensional flaky structure. The two-dimensional flaky structure can serve as a physical barrier to give the magnesium / magnesium alloy substrate excellent corrosion resistance. Figure 7 (d) and (e) are cross-sectional views of the self-sacrificial zinc oxide micro-arc oxidation coating and the composite coating, respectively. The self-sacrificial zinc oxide coating and the photothermal and metal ion synergistic antibacterial coating are both prepared by in situ growth, so the coatings are tightly connected and no stratification occurs.
[0133] like Figure 8 As shown, the XRD patterns of the AZ31 magnesium alloy material with a micro-arc oxidation coating (MAO) prepared in Comparative Example 2, the micro-arc oxidation coating covered with self-sacrificial zinc oxide prepared in Comparative Example 3, and the AZ31 magnesium alloy material with a composite coating prepared in Example 11 are shown. Figure 8 It can be seen that the composite coating prepared in Example 11 mainly contains ZIF-8 and MgO, indicating that 2-methylimidazole participates in the formation of the composite coating, but the ZIF-8 peak obtained by XRD is not a typical ZIF-8 peak, and some crystal faces disappear, which indicates that 3,4,9,10-perylenetetracarboxylic acid diimide also participates in the formation of the composite coating. The composite coating is mainly composed of a micro-arc oxidation coating and a photothermal and metal ion synergistic antibacterial coating.
[0134] like Fig. 9 As shown, the potentiodynamic polarization curves of the AZ31 magnesium alloy substrate, the AZ31 magnesium alloy material with a micro-arc oxidation coating (MAO) prepared in Comparative Example 2, and the AZ31 magnesium alloy material with a composite coating prepared in Example 11 are shown. Fig. 9 It can be seen that the self-corrosion current density of the AZ31 magnesium alloy material with the composite coating prepared in Example 11 is significantly reduced from 1.09×10-5A / cm 2 Down to 3.95×10-9A / cm 2 , indicating that the magnesium alloy material with composite coating has excellent corrosion resistance.
[0135] like Fig.10As shown, the left figure is the impedance curve of the AZ31 magnesium alloy substrate, the AZ31 magnesium alloy material with micro-arc oxidation coating (MAO) prepared in Comparative Example 2, and the AZ31 magnesium alloy material with composite coating prepared in Example 1, and the right figure is a partial enlarged view of the left figure. Fig.10 It can be seen from the comparison that the AC impedance of the AZ31 magnesium alloy material with the composite coating prepared in Example 11 is significantly increased compared with the magnesium alloy AZ31 without coating. The AC impedance of the AZ31 magnesium alloy material with the composite coating prepared in Example 11 is also significantly increased compared with the magnesium alloy AZ31 with micro-arc oxidation coating, indicating that the magnesium alloy material with the composite coating has excellent corrosion resistance.
[0136] like Fig.11 Shown are the temperature rise curves of the AZ31 magnesium alloy substrate and the AZ31 magnesium alloy material with a composite coating prepared in Example 11 in air and in Hank's solution, respectively. It can be seen from the figure that the magnesium alloy with the composite coating on the surface has excellent light and thermal properties.
[0137] like Fig.12 The cyclic photothermal curve of the AZ31 magnesium alloy material with composite coating prepared in Example 11 excited by 808nm near-infrared light in air is shown. Fig.12 It can be seen that the composite coating has excellent light and heat stability.
[0138] like Fig.13 The figure shows a comparison of the antibacterial properties of the AZ31 magnesium alloy substrate, the AZ31 magnesium alloy material with a micro-arc oxidation coating (MAO) prepared in Comparative Example 2, and the AZ31 magnesium alloy material with a composite coating prepared in Example 11 under no-light and light conditions. It can be seen from the figure that illumination is beneficial to improving the antibacterial properties of the AZ31 magnesium alloy; in addition, the AZ31 magnesium alloy material with the composite coating has antibacterial properties both under no-light conditions and under light conditions, compared with the AZ31 magnesium alloy substrate and the AZ31 magnesium alloy material with a micro-arc oxidation coating, and has better antibacterial properties under light conditions, which further illustrates that the hybrid coating that carries a large π aromatic system and has a centrally symmetrical perylene organic ligand coordinated with functional metal ions to form a two-dimensional planar molecule has good photothermal antibacterial properties.
[0139] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.
Claims
1. A magnesium / magnesium alloy material with an antibacterial and anticorrosive composite coating, comprising a magnesium / magnesium alloy substrate from the inside to the outside, characterized in that: It also includes micro-arc oxidation coating and antibacterial and anticorrosion coating; the antibacterial and anticorrosion coating is a photothermal, photodynamic and metal ion synergistic antibacterial and anticorrosion coating, or a self-sacrificial zinc oxide coating and a photothermal, photodynamic and metal ion synergistic antibacterial and anticorrosion coating; wherein the photothermal, photodynamic and metal ion synergistic antibacterial coating is a hybrid coating with a two-dimensional planar structure formed by loading a π aromatic system and centrally symmetrical porphyrin organic ligand, a functional ligand with a coordination site and a spatial volume smaller than that of the porphyrin organic ligand, and a functional polymer ligand with a coordination site; the self-sacrificial zinc oxide coating is an in-situ grown zinc oxide coating, and the photothermal, photodynamic and metal ion synergistic antibacterial coating is a hybrid coating with a two-dimensional planar structure formed by loading a π aromatic system and centrally symmetrical perylene organic ligand and a functional metal ion.
2. The magnesium / magnesium alloy material with an antibacterial and anticorrosive composite coating according to claim 1, characterized in that: The micro-arc oxidation coating is a phytic acid-based micro-arc oxidation coating.
3. The magnesium / magnesium alloy material with an antibacterial and anticorrosive composite coating according to claim 1, characterized in that: The porphyrin organic ligand with a π aromatic system and central symmetry carried by the photothermal, photodynamic, and metal ion synergistic antibacterial and anticorrosive composite coating is any one of meso-tetrakis(4-carboxyphenyl)porphyrin, 5,10,15,20-tetrakis(4-aminophenyl)porphyrin, tetraaldehyde phenylporphyrin, 5,10,15,20-tetrakis(4-methoxyphenyl)porphyrin, 5,10,15,20-tetrakis(4-cyanophenyl)porphyrin, 5,10,15,20-tetrakis(3,5-dihydroxyphenyl)porphyrin, and 5,10,15,20-tetrakis(4-hydroxyphenyl)-21H,23H-porphyrin; the functional ligand having a coordination site and a smaller spatial volume than the porphyrin organic ligand is pyrazine or 2-methylimidazole; The functional polymer ligand with coordination sites is polyvinyl pyrrolidone.
4. The magnesium / magnesium alloy material with an antibacterial and anticorrosive composite coating according to claim 1, characterized in that: The centrally symmetrical perylene organic ligand having a π aromatic system is any one of 3,4,9,10-perylenetetracarboxylic acid diimide, perylene-3,4,9,10-tetracarboxylic dianhydride or 4,4',4",4'-(perylene-2,5,8,11-tetrayl)tetrabenzoic acid.
5. The magnesium / magnesium alloy material with an antibacterial and anticorrosive composite coating according to claim 1, characterized in that: The functional metal ions are zinc ions, strontium ions, gallium ions, manganese ions, cerium ions, zirconium ions and selenium ions.
6. The method for preparing a magnesium / magnesium alloy material with an antibacterial and anticorrosive composite coating according to claim 1, characterized in that: The steps include: (a) Pretreatment: The magnesium alloy substrate was sanded with sandpaper until there were no obvious scratches on the surface, washed with deionized water and anhydrous ethanol, dried with cold air, placed in an oven, and taken out after constant temperature drying; (b) Preparation of micro-arc oxidation coating: (b1) dissolving phytic acid and sodium hydroxide in deionized water to prepare a micro-arc oxidation electrolyte solution; (b2) clamping the pretreated magnesium / magnesium alloy substrate between an anode and placing it in a micro-arc oxidation electrolyte solution, then passing a current and applying a high voltage to grow a phytic acid system micro-arc oxidation coating on the surface of the magnesium / magnesium alloy substrate; (c) Preparation of antibacterial and anticorrosive coating: A mixed solution of a hybrid coating having a two-dimensional planar structure formed by coordination of a π aromatic system and a centrally symmetrical porphyrin organic ligand, a functional ligand having a coordination site and a smaller spatial volume than the porphyrin organic ligand, and a functional polymer ligand having a coordination site and a functional metal ion is prepared; The magnesium / magnesium alloy coated with the micro-arc oxidation coating prepared in step (b) is immersed in the mixed solution of the hybrid coating, and subjected to hydrothermal treatment at 70 to 90° C. for 20 to 25 hours, and a layer of photothermal, photodynamic, and metal ion synergistic antibacterial coating is in situ grown on the surface of the micro-arc oxidation coating with the micro-arc oxidation coating as an intermediate layer, and the coating is taken out, rinsed, and blown dry; The magnesium / magnesium alloy material covered with the micro-arc oxidation coating and the photothermal, photodynamic, and metal ion synergistic antibacterial and anticorrosion coating is placed in an oven for drying, and taken out after constant temperature drying treatment to obtain a magnesium / magnesium alloy material with a photothermal, photodynamic, and metal ion synergistic antibacterial and anticorrosion composite coating; Alternatively, (c1) is prepared from a sacrificial zinc oxide coating: Prepare zinc nitrate solution; The magnesium / magnesium alloy coated with the micro-arc oxidation coating prepared in step (b) is immersed in the zinc nitrate solution prepared in step (c1), and subjected to hydrothermal treatment at 110-130° C. for 3-5 hours to in-situ grow a layer of zinc oxide coating on the surface of the micro-arc oxidation coating, and then taken out, rinsed, and dried; The prepared magnesium / magnesium alloy coated with the micro-arc oxidation coating and the zinc oxide coating is placed in an oven for drying, and taken out after being dried at a constant temperature; (c2) preparing a hybrid coating solution loaded with a π aromatic system and a centrosymmetric perylene organic ligand coordinated with a functional metal ion to form a two-dimensional planar structure: A deionized water solution containing a perylene organic ligand having a π aromatic system and central symmetry and 2-methylimidazole is prepared; The micro-arc oxidation magnesium / magnesium alloy coated with zinc oxide coating prepared in step (c1) is immersed in a deionized water solution containing a perylene organic ligand having a π aromatic system and central symmetry and 2-methylimidazole, and subjected to hydrothermal treatment at 110-130° C. for 3-5 hours, and a layer of photothermal and metal ion synergistic antibacterial coating is in situ grown on the surface of the micro-arc oxidation coating with the zinc oxide coating as a self-sacrificial layer, and the coating is taken out, rinsed, and blown dry; The prepared magnesium / magnesium alloy material covered with a micro-arc oxidation coating, a self-sacrificial zinc oxide coating, and a photothermal and metal ion synergistic antibacterial coating is placed in an oven for drying, and taken out after constant temperature drying treatment to obtain a magnesium / magnesium alloy material with a photothermal and metal ion synergistic antibacterial and anticorrosive composite coating.
7. The method for preparing a magnesium / magnesium alloy material with an antibacterial and anticorrosive composite coating according to claim 6, characterized in that: In the step (b1), the concentration of phytic acid is 5-10 g / L, and the concentration of sodium hydroxide is 5-15 g / L.
8. The magnesium / magnesium alloy material with an antibacterial and anticorrosive composite coating according to claim 6, characterized in that: In the step (b2), the voltage is 400 V, the current is 1 A, and the duty cycle is 20%.
9. The magnesium / magnesium alloy material with an antibacterial and anticorrosive composite coating according to claim 6, characterized in that: The concentration of zinc nitrate is 10-11 g / L; the concentration of 2-methylimidazole is 100-110 g / L.
10. The magnesium / magnesium alloy material with an antibacterial and anticorrosive composite coating according to claim 6, characterized in that: The total thickness of the micro-arc oxidation coating and the antibacterial and anti-corrosion coating is 5 to 6 um.